Limb salvage in soft tissue sarcomas - Temple, Walley J. (Radiology and oncology (Ljubljana), 2000)
In 2000, most patients with soft tissue sarcomas of the axial or appendicular skeleton can expect 'to walk away' from the surgery. This compares to just 20 years ago when a relatively high percentage of patients were treated with amputation. Now the treatment has changed to one of wide local excision with a1 cm to 2 cm margin on normal tissues and an adventitial margin on critical structures such as nerves or vessels, followed or preceded by radiotherapy. With the use of adjuvant treatments in combination with reconstructive surgery, over 90% of patients with sarcomas of the soft tissues or bone may berendered disease free locally. The only restriction to this approach is whentumor involves the major nerve to a limb or when microscopic, clear margins cannot be obtained at the time of surgery as both of these are best treated with an imputation.
Keywords: Extremities; kirurško zdravljenje; Neoplasm staging; okončine; rak (medicina); Sarcoma; sarkom; Soft tissue neoplasms; Surgery; Survival analysis